Outcome Based Education and its Modifications to Suit Eastern Countries - D. Ananth Padmanabhan; T.R. Vijayaram; N. Ramya (International Journal of Education Sciences, 2024)
A higher education strategy known as “outcome-based education” (OBE) is centered on assessing the effects and consequences of learning. It has been widely adopted and followed in several countries particularly in vocational and professional education. In this research, the state of outcome-based education—which combines traditional and content-based learning methods—in educational institutions is examined. Assuring that students obtain a top-notch education that equips them for success in their future occupations is made possible in large part by examining the status of OBE in educational institutions. A systematic structure for education, a particular approach to instructional practice, and an educational theory are the three main ways that OBE differs from standard education methods. It arranges the whole educational system around the things that are thought to be necessary for students to be able to do well when they finish their studies. OBE is proven to improve the quality of teaching and learning, competitiveness among graduates and English language proficiency of the students. The purpose of this schooling was to give the younger students access to the knowledge and abilities of an older generation while also creating a conducive learning atmosphere. The curriculum is decided upon by outcome-based education based on the competencies that students should exhibit at the conclusion of their program. As a result, the course offered, the educational environment, the teaching strategies, the content and organization of the curriculum, and the assessment techniques are all determined by the outcomes or competencies. Traditional teaching methods were output based and it is changing to outcome-based education. Education with an outcome focus is here to stay. Student-centric learning has replaced teacher-centric learning. This review paper examines outcome-based education in detail and compares the changes taking place in society in line with outcome based education.
Keywords: Attainment; Course Outcomes; Design-Down Approach; Learner Experience; Outcome Based Education; Program Evaluation; Program Outcomes; Student Evaluation